Por uma dialética de permanente ecocentrização do constitucionalismo ambiental brasileiro: uma interlocução entre a constituição de 1988 e o estado ecológico de Klaus Bosselmann - Câmara, Ana Stela Vieira Mendes (2016)
The existence of an unprecedented environmental crisis in the history of mankind has led to many reflections on how states should incorporate the environmental preservation, in order to prevent or minimize its effects. From discussions in Germany, it comes Klaus Bosselmann’s contribution, which advocates the need to overcome the anthropocentrism as the only possible condition for the formulation of a really sustainable alternative of political and social organization. On that basis, and taking into account its political, legal and economic implications, the author elaborates the model of the Ecological State. Although this model does not reflect the current Brazilian constitutional choice, the aim of this doctoral thesis is to demonstrate the feasibility of building a dialogue between the Ecological State and Brazilian environmental constitutionalism, which is ethically syncretic in its genesis, to enable new horizons for overcoming the ecological crisis now established. The specific objectives are developed over the five chapters, namely: briefly describing the integration of environmental concerns in nuclear issues of the State, with its ethical foundations; presenting a detailed and systematic way the design of the Ecological State, from Bosselmann’s assumptions in theoretical and epistemological, economic, political and legal fields; gathering critical to the model studied when it comes to its ethical aspects, legal, political and economic, looking expose answers to the questions raised, both from the Bosselmann’s thought itself, as throught the dialogue with other authors; defending current possibilities of reading Brazilian environmental constitutional order according to the model studied, passing by a contextual analysis of Constitution’s promulgation, by the systematic study of its text, which demonstrates the feasibility of a fruitful dialogue; and finally report some facts that point to difficulties and challenges to be faced in connection with its implementation, such as evidence of insufficient protection by public policy, recent legislative regressions, and also investigate the potentials and limits of role of the judiciary in this context. Regarding methodology, we used a qualitative, theoretical, comparative, bibliographical, documental, explanatory and transdisciplinary approach, with the use of some case studies and dialectical methodology inductive predominance. We analysed national and foreign doctrine that have fled the anthropocentric route, as well as national legislation and jurisprudence, in addition to extensive search in documents and official data.